Watercolor flowers : a modern exploration of the color wheel and watercolor to create beautiful floral artwork - Mishra, Manushree (Contemporary color theory., 2022)
Contemporary Color Theory: Watercolor Flowers teaches beginning and aspiring artists the basics of color theory and color mixing, and includes step-by-step watercolor painting projects featuring beautiful florals.